2012
DOI: 10.1016/j.nbd.2012.04.012
|View full text |Cite
|
Sign up to set email alerts
|

K+ channel alterations in the progression of experimental autoimmune encephalomyelitis

Abstract: Voltage-gated K+ (Kv) channels play critical roles not only in regulating synaptic transmission and intrinsic excitability of neurons, but also in controlling the function and proliferation of other cells in the central nervous system (CNS). The non-specific Kv channel blocker, 4-AminoPyridine (4-AP) (Dalfampridine, Ampyra®), is currently used to treat multiple sclerosis (MS), an inflammatory demyelinating disease. However, little is known how various types of Kv channels are altered in any inflammatory demyel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 68 publications
1
48
0
Order By: Relevance
“…The procedure of cardiac perfusion, tissue fixation and sectioning were previously described (Jukkola et al, 2012; Jukkola et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The procedure of cardiac perfusion, tissue fixation and sectioning were previously described (Jukkola et al, 2012; Jukkola et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…There are a number of K + channels implicated in astrocytes. We recently showed that Kv1.4 is highly upregulated in activated astrocytes within and surrounding lesions in the spinal cord of mice induced with EAE [33]. Kv1.6 expression has been reported in astrocyte culture [125] but does not appear to be altered in reactive astrocytes [126].…”
Section: Astrocyte Channel Proteinsmentioning
confidence: 99%
“…Furthermore, other K + channels, including two-pore and Ca 2+ -sensitive K + channels, are also found in astrocytes [2832]. Voltage-gated Kv1.4 channels are highly upregulated in activated astrocytes around experimental autoimmune encephalomyelitis (EAE; an animal model of MS) lesions [33], although their functional role in this context remains unclear. Astrocytes can participate in cell-to-cell communication by propagation of Ca 2+ waves [34, 35], which require channel proteins in the plasma membrane and endoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 99%
“…Coronal sections (40-mm thickness) of mouse cerebellum were cut with a Microm HM550 cryostat (Thermo Scientific, Waltham, MA) and collected on Superfrost Plus microscope slides (FisherScientific, Pittsburgh, PA). Immunostaining and imaging were performed as previously described (Jukkola et al, 2012). The whole images captured with a 406 objective lens were processed for quantification using Metamorph by flattening the background, thresholding the images to include only the 5% highest intensity pixels, and binarizing the image.…”
Section: Kv31 Knockout Mouse Genotypingmentioning
confidence: 99%